2007
DOI: 10.1103/physreva.75.043603
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a coupled two-species atom–heteronuclear-molecule condensate

Abstract: We study the coherent association of a two species atomic condensate into a condensate of heteronuclear diatomic molecules, using both a semiclassical treatment and a quantum mechanical approach. The differences and connections between the two approaches are examined. We show that, in this coupled nonlinear atom-molecule system, the population difference between the two atomic species play significant roles in the ground state stability properties as well as in coherent population oscillation dynamics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
(113 reference statements)
1
23
0
Order By: Relevance
“…As in other studies [18,19], Eqs. (10) of the type including Feshbach resonance support two branches of steady-states: one with θ = 0 and the other with θ = π.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As in other studies [18,19], Eqs. (10) of the type including Feshbach resonance support two branches of steady-states: one with θ = 0 and the other with θ = π.…”
Section: Discussionsupporting
confidence: 57%
“…[23] for a heteronuclear atom-molecule system with an interspecies Feshbach resonance [18]. It simply reflects the fact that for bistability to take place, there must be a sufficiently strong positive feedback between the molecular population and the effective Feshbach detuning ǫ + χn.…”
Section: Discussionmentioning
confidence: 99%
“…These results boosted the search for solvable models that could describe some of the BEC properties [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The rationale beneath these studies is that through exactly solvable models it is possible to fully take into account quantum fluctuations, going beyond the usual mean field approximations.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier paper [22], we have concentrated on the coherent creation of heteronuclear molecular condensates (similar studies can also be found in reference [23]). In this paper, we will focus on constructing zerotemperature phase diagrams, paying particular attentions to phase separation and collapse.…”
Section: Introductionmentioning
confidence: 99%